The Role of the Internet in the Academic Pursuit of University Students: A Study of Ahmadu Bello University, Zaria and Bayero University, Kano, Nigeria. - Gana, Emmanuel Tsadu; Gana, Makun (NIU Journal of Humanities, 2018)
In this work, the researchers sought to seek the current and potential impact of the Internet on students of Nigeria tertiary educational system, through the role of the Internet in the academic pursuit of university students using Ahmadu Bello University Zaria and Bayero University Kano as study. The aim of the study therefore is to establish the correlation between Internet usage and student academic performance. A well-structured questionnaire was randomly distributed to one thousand (1000) students of both ABU Zaria (700) and BUK (300) with a response rate of 583 and 280 for ABU and BUK respectively. In concluding our findings, several variables were put into consideration such as, the rate at which students use the Internet and whether the Internet can assist students to acquire knowledge, and the role of Internet access in the academic pursuit of students. The study was able to establish that the youths, especially students, use the Net in ways that enhance their academics.